Delicts "contra sextum Decalogi praeceptum": Historical Development and Canonical Application - Mulheron, Susan Michelle; Pontificia Universitas Sanctae Crucis Facultas Iuris Canonici (Roma Ed. Università della Santa Croce, 2023)
The decision of the supreme legislator to use the phrase “delict against the sixth commandment of the Decalogue” to describe sexual misconduct or crimes is one that is not without criticism. In recent decades, much has changed in the Church’s law dealing with sexual delicts of clergy, but reference to these offenses as delicts contra sextum has not. This study takes a historical approach to assessing the evolution of the Church’s law and culture in regard to dealing with clerical sexual misconduct. By studying how these laws were written at various points in the history of the Church, with detailed attention to when modifications were made and for what motivations, we can better understand the mens legislatoris—why the law was drafted as it was in the past, and by extension, why it is written how it is today. This study demonstrates that the phrase contra sextum Decalogi praeceptum did not come into common use in canon law to describe sexual crimes until its abrupt inclusion in the canons of the first code of canon law promulgated in 1917. It provides a detailed recounting and analysis of the draft canons as they progressed through various revision processes since the time of the First Vatican Council. Tables are included that illustrate the various changes made to the legal text at various points, in order to better understand the mindset and approach of those responsible for forming the law. By analyzing the drafting and revision process of these norms, we can gain insight into the concerns, priorities, culture, and values of the Church over time in regard to regulating sexual misconduct and delictual behavior of clergy, and apply that knowledge to the interpretation and practice of the law today.
Dissertation
Keywords: Hochschulschrift